Cloning genes encoding chitinase 42 kDa of Trichoderma asperellum into the plant expression vector pMYV719 for genetic transformation - Phùng , Thị Bích Hòa; Nguyễn, Hoàng Tuệ; Phạm , Thị Huyền Trang; Trần, Gia Cát Tường; Huỳnh, Thị Huyền Trang; Nguyễn , Xuân Huy; Nguyễn , Hoàng Lộc (Hue University Journal of Science: Natural Science, 2022)
In this study, chitinase genes containing a signal peptide sequence, such as Chi42, syncodChi42-1 and syncodChi42-2, were cloned in the plant expression vector pMYV719 and successfully transferred into Agrobacterium tumefaciens LBA 4404. Among them, Chi42 is a wild-type gene of Trichoderma asperellum SH16. Both genes syncodChi42-1 and syncodChi42-2 are derived from Chi42, which was optimized for codon usage for plant expression. Agrobacterium bacteria-harbouring pMYV719/chitinase vector was used for genetic transformation into peanuts (Arachis hypogaea L.) to enhance resistance to phytopathogenic fungi in further studies.